Role of Financial Risks in BOT Megatransportation Projects in Developing Countries - Aladag, Hande; Isik, Zeynep (ASCE-AMER SOC CIVIL ENGINEERS, 2017)
The financial resources required to invest in high-budget infrastructural projects increase the interest in build-operate-transfer (BOT) models. Megatransportation projects, in which BOT is commonly used as a financial model, are seen as potentially important because of the considerable impact they have on the construction industry. Therefore, it is crucial to determine and manage the financial risks in these projects. In this context, the aim of this paper is to investigate the role of financial risks based on the criteria of success in BOT megatransportation projects from the point of the concessionaire. Therefore, financial risks were determined and then ranked by using the technique for order preferences by similarity to ideal solutions (TOPSIS) method. Then, the validity of determined financial risks was tested in an ongoing BOT mega-airport project by using the case study method. The prominent risk factors were the finance issues related to design changes and occupational safety and health, bankruptcy/insolvency of one of the private partners, currency risk, and fluctuation of the inflation rate. (C) 2017 American Society of Civil Engineers.
Keywords: Risk management; Financial risk; Build-operate-transfer (BOT); Transportation projects; Construction industry; Technique for order preferences by similarity to ideal solutions (TOPSIS) case study; PUBLIC-PRIVATE PARTNERSHIPS; INFRASTRUCTURE PROJECTS; ALLOCATION; STRATEGIES; MODEL; Engineering